The effects of age, height and gender on the somatosensory evoked potentials in man - (:unkn) unknown (My University, 1996)
Somatosensory evoked potentials (SEPs) reflect the activity of somatosensory pathways mediated through the dorsal columns of the spinal cord and the specific somatosensory cortex. In this study we aimed to demonstrate the effects of physiologic parameters such as height, age and gender on N9, N13, N20 SEP components and the central conduction time (CCT) to median nerve stimulation in Turkish population. The results revealed a statistically significant correlation between height, gender and SEP latencies (p < 0.05 and p < 0.0005 respectively) whereas no significant age related changes was found in SEPs. In all groups CCT was not influenced by these parameters.
Keywords: Adult; Female; Humans; Middle Aged; Male; Age Factors; Reaction Time; Sex Factors; Body Height; Evoked Potentials, Somatosensory